2020
DOI: 10.4049/jimmunol.1901119
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Antigens to Different Receptors on Conventional Type 1 Dendritic Cells Impacts the Immune Response

Abstract: Targeting Ag to surface receptors on conventional type 1 dendritic cells can enhance induction of Ab and T cell responses. However, it is unclear to what extent the targeted receptor influences the resulting responses. In this study, we target Ag to Xcr1, Clec9A, or DEC-205, surface receptors that are expressed on conventional type 1 dendritic cells, and compare immune responses in BALB/c and C57BL/6 mice in vitro and in vivo after intradermal DNA vaccination. Targeting hemagglutinin from influenza A to Clec9A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 64 publications
(103 reference statements)
3
38
0
Order By: Relevance
“…If the goal is to orchestrate a Th1 type immunity, targeting cDC1s through the XCR1 or CLEC9a receptor seems an attractive option [142]. The recent results of Oba et al [143] demonstrate that in situ induction and activation of cDC1s by Flt3L and TLR3/CD40 stimulation facilitates priming, expansion and infiltration of tumour‐specific T cells in poorly infiltrated tumours and renders those tumours responsive to anti‐PD‐L1 therapy.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
“…If the goal is to orchestrate a Th1 type immunity, targeting cDC1s through the XCR1 or CLEC9a receptor seems an attractive option [142]. The recent results of Oba et al [143] demonstrate that in situ induction and activation of cDC1s by Flt3L and TLR3/CD40 stimulation facilitates priming, expansion and infiltration of tumour‐specific T cells in poorly infiltrated tumours and renders those tumours responsive to anti‐PD‐L1 therapy.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
“…Several immunophenotypic subsets of DCs have also been identified with cDCs consisting of either CD141 + or CD1c + cells 25 . Prior studies have demonstrated that expression of associated receptors of antigen presentation determines the effectiveness of antigen cross presentation 26 and targeting these receptors influences immune response 27 . These advances in our understanding of DC biology have led to novel vaccination strategies that utilize antigen‐conjugated antibodies targeting antigens to human DCs with DEC‐205 and Clec9A emerging as promising targets 28 .…”
Section: Biologymentioning
confidence: 99%
“…DEC205 (CD205) is a C-type lectin endocytic receptor expressed on thymic epithelial cells and on cDC1s 14 , 15 . cDC1s reside in the T cell areas of the lymphoid organs and have a high capacity to cross-present antigens to CD8 + T cells 16 . Other approaches to deliver antigens to cDC1s, such as Clec9A, Xcr1 and STxB-based vaccines are known to induce strong antigen-specific B and T cell responses, even in the absence of an adjuvant 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…cDC1s reside in the T cell areas of the lymphoid organs and have a high capacity to cross-present antigens to CD8 + T cells 16 . Other approaches to deliver antigens to cDC1s, such as Clec9A, Xcr1 and STxB-based vaccines are known to induce strong antigen-specific B and T cell responses, even in the absence of an adjuvant 16 , 17 . Nonetheless, targeting antigens to DEC205 + DCs is usually not sufficient to activate strong antigen-specific immune responses, requiring the use of an additional innate immunity stimulus for cell activation and maturation 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%